The White Lotus TV Series Season 2: Deconstructing Italians Stereotypes - Alfarisy, Fitri; Helena Sirait, Yosephine (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
Modern mass media serve as both a "magic window" into the world and a "door" to new ideas. It is important to look at how the steady growth of media affects the way racial and cultural stereotypes are pushed forward. Stereotypes themselves can influence how people view facts and social events and one of many examples of stereotypes is Italian stereotypes. This study analyzes HBO's popular series, The White Lotus season two, employing Fairclough's model critical discourse analysis to deconstruct Italian stereotypes through the characters' portrayals. This study also examines the sociocultural aspect and physical appearances of the Italian characters portrayed by American television. The findings of this study show the physical portrayal of Italians mostly they have the same features and are known for their fashion sense and attention to appearance. Moreover, Italian characters are portrayed with speak loudly and having the urge to cause some disturbance. The last stereotype is quite expected but debatable, which is the portrayal of Italians being middle-class workers and mafia. This stereotype had some audience feeling disappointed and others pleased enough. Western films' mafia stereotypes could affect how people learn about the culture, and think all Italians are dangerous, poor, and do drugs. Mafias exist and should not define Italian identity, especially in mainstream media.